2015
DOI: 10.1093/cesifo/ifv019
|View full text |Cite
|
Sign up to set email alerts
|

Early Birds in Day Care: The Social Gradient in Starting Day Care and Children’s Non-cognitive Skills

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Studies in the economic literature show an increase in the likelihood of transiting to secondary schooling, college graduation, and higher wages for individuals with trait sets 'emphasizing' openness, conscientiousness, or extroversion (Mueller and Plug, 2006;Borghans et al, 2008;Baron and Cobb-Clark, 2010;Heineck and Anger, 2010;Almlund et al, 2011;Lundberg, 2013;Fletcher, 2013). Looking at findings from the literature on short run childcare effects on non-cognitive skills, Peter et al (2016) show that children in England who enter childcare early are more prosocial and experience fewer peer problems at the age of five and seven. Given that children in childcare more frequently interact with other peers and adults than they would have when not attending, we hypothesize that one additional year of universal childcare attendance might most likely affect the level of students' personality trait dimensions extroversion and openness to new experience in the long run.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies in the economic literature show an increase in the likelihood of transiting to secondary schooling, college graduation, and higher wages for individuals with trait sets 'emphasizing' openness, conscientiousness, or extroversion (Mueller and Plug, 2006;Borghans et al, 2008;Baron and Cobb-Clark, 2010;Heineck and Anger, 2010;Almlund et al, 2011;Lundberg, 2013;Fletcher, 2013). Looking at findings from the literature on short run childcare effects on non-cognitive skills, Peter et al (2016) show that children in England who enter childcare early are more prosocial and experience fewer peer problems at the age of five and seven. Given that children in childcare more frequently interact with other peers and adults than they would have when not attending, we hypothesize that one additional year of universal childcare attendance might most likely affect the level of students' personality trait dimensions extroversion and openness to new experience in the long run.…”
Section: Introductionmentioning
confidence: 95%
“…Given that in the European context nearly all children above the age of three attend childcare today, the current literature examines more refined measures of childcare enrollment, such as entrance age, duration of childcare, or dosage of childcare, i.e. half day versus full day attendance (e.g Loeb et al, 2007;Müller et al, 2013;Peter et al, 2016). In this paper, we further contribute to this strand of the literature by analyzing the causal effect of early childcare entrance, the effect of one additional year of childcare, on personality traits in the long run.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results are conflicting. For instance, Peter et al (2016) found centre-based care entry later than at the age of 2;5 years in the UK to be associated with lower prosocial behaviour and increased peer problems at the age of 7 years. Furthermore, Linberg et al (2019a) found more years spent in early centre-based care under the age of 3 years to be significantly related to lower rates of peer problems in Germany.…”
Section: Cross-country Differencesmentioning
confidence: 99%
“…However, small positive effects of the formal child care attendance of any type at nine months on socio-emotional skills at the age of 5 years were also documented (Russell et al, 2016 ). Furthermore, the fact of attending early formal child care more than one year under the age of three years was associated with lower rates of peer problems as rated by parents – but not with prosocial behaviour – of 3-year-old children in Germany (Linberg et al, 2019 ), while later entry in formal child care (i.e., later than the age of 29 months) was related to increase of parental-rated peer problems and reduction of prosocial behaviour of 7-year-old children in the United Kingdom (Peter et al, 2016 ). Notably, there are studies which found no effects of formal child care attendance on socio-emotional skills (e.g., Del Bono et al, 2016 , investigating socio-emotional skills of 7-year-old children in the United Kingdom).…”
Section: Factors Influencing Early Socio-emotional Outcomesmentioning
confidence: 99%